Secretome and degradome profiling shows that Kallikrein‐related peptidases 4, 5, 6, and 7 induce TGFβ‐1 signaling in ovarian cancer cells. Issue 1 (1st October 2013) - Shahinian, Hasmik; Loessner, Daniela; Biniossek, Martin L.; Kizhakkedathu, Jayachandran N.; Clements, Judith A.; Magdolen, Viktor; Schilling, Oliver
Abstract : Kallikrein‐related peptidases, in particular KLK4, 5, 6 and 7 (4–7), often have elevated expression levels in ovarian cancer. In OV‐MZ‐6 ovarian cancer cells, combined expression of KLK4–7 reduces cell adhesion and increases cell invasion and resistance to paclitaxel. The present work investigates how KLK4–7 shape the secreted proteome ("secretome") and proteolytic profile ("degradome") of ovarian cancer cells. The secretome comparison consistently identified >900 proteins in three replicate analyses. Expression of KLK4–7 predominantly affected the abundance of proteins involved in cell–cell communication. Among others, this includes increased levels of transforming growth factor β‐1 (TGFβ‐1). KLK4–7 co‐transfected OV‐MZ‐6 cells share prominent features of elevated TGFβ‐1 signaling, including increased abundance of neural cell adhesion molecule L1 (L1CAM). Augmented levels of TGFβ‐1 and L1CAM upon expression of KLK4–7 were corroborated in vivo by an ovarian cancer xenograft model. The degradomic analysis showed that KLK4–7 expression mostly affected cleavage sites C‐terminal to arginine, corresponding to the preference of kallikreins 4, 5 and 6. Putative kallikrein substrates include chemokines, such as growth differentiation factor 15 (GDF 15) and macrophage migration inhibitory factor (MIF). Proteolytic maturation of TGFβ‐1 was also elevated. KLK4–7 have a pronounced, yet non‐degrading impact on the secreted proteome, with a strong association between these proteases and TGFβ‐1 signaling in tumor biology. Highlights: Expression of KLK4, 5, 6, and 7 yields subtle secretome and degradome alterations. Pro‐ and anti‐tumorigenic proteins are affected. TGFβ‐1 signaling is elevated. Degradomic analysis supports cell‐contextual KLK activity. Potential substrates of KLK4–7 have been identified.